TINJAUAN SIYASAH MALIYAH DALAM PENGELOLAAN DANA RETRIBUSI PARKIR DI KOTA BANDA ACEH - Wira Asfahani Merina; Mumtazinur Mumtazinur; Azka Amalia Jihad (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to examine the management of parking retribution in Banda Aceh City within the framework of siyasah maliyah as a branch of Islamic public finance governance. Normatively, the study is based on the premise that every fiscal policy in Islam must adhere to the principles of justice, trustworthiness, transparency, accountability, and public welfare. The research employs a qualitative method through a library study approach, analyzing both classical and contemporary literature on fiqh siyasah, as well as local regulations, particularly Qanun No. 3 of 2021 and Mayor Regulation No. 22 of 2024. The findings indicate that although the regulatory framework is well established and the digitalization of the parking system has been initiated, the implementation of siyasah maliyah principles remains inadequate. Weak monitoring, the persistence of illegal levies, and the unequal distribution of benefits are still prevalent. The study concludes that reinforcing Sharia-based governance is essential so that parking retribution serves not only as a fiscal instrument to increase local revenue but also as a means of ensuring equitable economic distribution and improving public services in line with Islamic principles.